Capitalism, competition and economic crisis : structural changes in advanced industrialised countries - Brenner, Y. S. (Brighton, England : Wheatsheaf Books, 1984)
The subject of the book is complex. It involves the examination of social, political, political and psychological developments in an attempt to explain the current economic crisis. As the title of the book indicates, little attention is paid to the problems of economically underdeveloped countries, since the book is concerned with developments which affect industrialised societies.
Includes bibliographical references and index.
rpm 06/11/2017
Loans
Keywords: Economic history -- 1971-1990.; Capitalism; Economic order; Business cycle